FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KESIAPAN IBU HAMIL DALAM MENGHADAPI PERSALINAN DI RSIA SITI KHADIJAH MAKASSAR - Nurhikmah Nurhikmah (Stikes Graha Edukasi Makassar, 2021)
Objective: The purpose of this study was to look at factors related to maternal preparedness in facing childbirth at RSIA Khadijah I Makassar. Method: In this study used the research design used in this study is cross sectional that researchers do observation or measurement of variables at one time. Population in this research as much 50. And where big sample in this research 50 respondents that match with inclusion criteria. The data were collected by using questionnaires. Results: The results showed that there was a relationship between family support and maternal preparedness (p = 0,005), there was a relationship between ANC visit with pregnant woman's readiness (p = 0,007), and there was correlation between knowledge with pregnant woman's readiness (p = 0,000). Discussion: Labor is a process of expending the results of conception that can live in the outside world, from the womb through the birth canal or by other means performed by health workers. Conclusion: The conclusion in this study is that there is a relationship between family support, ANC visits and knowledge with the readiness of pregnant women. Suggestion: Suggestion The results of this study can improve insights and knowledge of nurses to be able to provide comprehensive and professional nursing care